SOE operations in Albania during the Second World War - Marian Zidaru (Technium Social Sciences Journal, 2020)
After Mussolini entered World War II on the side of Hitler, the British sent a colonel into Albania in April 1941 to help the resistance, but he was soon captured. It would not be until April 16, 1943, that two more SOE officers, Lt. Col. Neil McLean and Captain David Smiley, parachuted into northern Greece and crossed the border. Others would follow, including a former lieutenant in the Spanish Foreign Legion, Peter Kemp; Himalayan explorer Bill Tillman; and Reginald Hibbert, whose view of events in Albania in the years to come would put him bitterly at odds with his fellow SOE officers. SOE operations were hampered by woeful British ignorance about Albania. London had only a lower-level diplomatic presence there before the Italian occupation, and the main source of information had been an elderly Englishwoman who had lived there for 20 years. This paper told the story of SOE operations in Albania.